Interventional treatment for structural heart disease: who is deciding, and can we afford it? (Swiss Medical Weekly, 2014)
During the last years, the numbers of interventions in structural heart disease such as transcatheter aortic valve implantation (TAVI), percutaneous treatment of mitral regurgitation using the MitraClip, closure of atrial septal defects (ASD) and others have constantly increased. While the 20th century was called the century of surgery, it appears that the present century might be the century of minimally invasive percutaneous therapy. The reduced invasiveness of these procedures and the success in elderly patients make these treatments increasingly attractive for younger and healthier patients. Now that these procedures are moving forward, some questions arise, namely, who is deciding on treatment modality, and can we afford it?